2016
DOI: 10.1177/1687814015624846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of direct-current electric fields on flame shape and combustion characteristics of ethanol in small scale

Abstract: The aim of this work is to investigate the effects of direct-current electric fields on the behavior of the small-scale diffusion ethanol flame. The flow rate of liquid ethanol, the flame temperatures, and the flame shapes were measured. The results showed that the stable working ranges of a small-scale combustor became narrower under the direct-current electric field. The main reason was that the evaporation velocity of liquid ethanol limited by great heat loss effect cannot keep up with the increasing of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…Energy: In our previous work [28], it was found that the external electric energy was very small compared with the actual burning thermal energy of ethanol in this study. This was also mentioned in the reference [22].…”
Section: Experimental Systemmentioning
confidence: 58%
See 2 more Smart Citations
“…Energy: In our previous work [28], it was found that the external electric energy was very small compared with the actual burning thermal energy of ethanol in this study. This was also mentioned in the reference [22].…”
Section: Experimental Systemmentioning
confidence: 58%
“…So the temperature at the top position was chosen to represent the flame temperature. Moreover, the measurement at the top position brought the smallest disturbance to the flame compared with other positions[28].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Research on the effects of a dc field on a hydrocarbon flame has been done by many researchers [12][13][14][15][16][17][18][19]. Results have shown the electric field capable of increased lean blowoff limits, increased flame burning velocity, decreased emissions and soot formation, and enhanced flame stability.…”
Section: Nomenclaturementioning
confidence: 99%
“…The use of the electric field (EF) to control the combustion characteristics for different types of hydrocarbon fuels (gaseous, liquid, solid) is considered as an effective tool to provide the local variations of flow dynamics, flame shape, structure, composition, temperature, heat output and composition of emissions, as well to improve the flame [1][2][3]. The results of the experimental study and theoretical analysis suggest that the main mechanism, which leads to the variation of the combustion dynamics can be related to the ion wind effect, when the electric field-induced body force initiates the acceleration of the flame ions (CHO + , H 3 O + , C 2 H 3 O + , O 2 -, OH -, CHO 3 -) in the field direction with subsequent momentum transfer to neutral flame species [1].…”
Section: Introductionmentioning
confidence: 99%